2015
DOI: 10.7314/apjcp.2015.16.15.6599
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Kinase (CK)-MB-to-Total-CK Ratio: a Laboratory Indicator for Primary Cancer Screening

Abstract: Background: For the determination of creatine kinase (CK)-MB, the immunoinhibition method is utilized most commonly. However, the estimated CK-MB activity may be influenced by the presence of CK isoenzymes in some conditions like cancer. Thus, a CK-MB-to-total-CK ratio more than 1.0 could be found in such a situation. The study aimed to explore the relationship of cancer to high CK-MB-to-total-CK ratio. Materials and Methods: From January 2011 to December 2014, laboratory data on all CK-MB and total CK test re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Most often, its components entail CK-BB and monoclonal IgG. 2,3 All except macro CK type 2 consist of a normal enzyme complexed with an immunoglobulin, most commonly IgG or IgA. The complexed enzyme has reduced blood clearance, resulting in increased circulating amounts of the higher-than-normal molecular weight form of the relevant enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, its components entail CK-BB and monoclonal IgG. 2,3 All except macro CK type 2 consist of a normal enzyme complexed with an immunoglobulin, most commonly IgG or IgA. The complexed enzyme has reduced blood clearance, resulting in increased circulating amounts of the higher-than-normal molecular weight form of the relevant enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this amalgamated molecule may interfere with commonly used biochemical assays by adding to the estimation of CK-MB but not to the total CK.7 Conversely, high levels of total CK with a normal CK-MB have also been described in the literature. 2,4 Irrespective of the macro-CK subtype, a retrospective study by the Change et al, concluded that approximately 40% of the patients with the CK-MB: total CK ratio greater than the 1 had the underlying malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the three different cytosolic isoenzymes formed by the various combinations of M (muscle) and B (brain) subunits in the cytosol are-CK-MM, CK-MB and CK-BB. [1][2][3][4][5][6] The CK-MM is mainly found in all kinds of muscle cells, CK-MB mainly in the myocardial cells and CK-BB exists mainly in the brain cells. 3 The distribution of various isoenzymes in the serum of healthy individuals is:-CK-MM (96-100%), CK-MB (0-6%) and CK-BB is almost undetectable.…”
Section: Introductionmentioning
confidence: 99%
“…3 The distribution of various isoenzymes in the serum of healthy individuals is:-CK-MM (96-100%), CK-MB (0-6%) and CK-BB is almost undetectable. 6 Apart from these cytosolic enzymes, a mitochondrial isoenzyme of CK (CKm) is found in muscle, brain and cerebrospinal fluid. 2 The creatine kinase isoenzyme CKMB is cardio-specific and is accepted as the most sensitive and specific indicator of myocardial cell necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, CK-MB activity measured using an immunoinhibition technique may exceed the upper-normal limit, whereas CK-MB mass measurements of the same sample may be in the normal range. Many laboratories still use immunoinhibition as the routine method to measure CK-MB activity in serum for several reasons [4,5]. In Izmir, the third largest city in Turkey, about 100.000 CK-MB activity tests per year are performed in 15 different state hospitals.…”
mentioning
confidence: 99%